Clinical protocol. Administration of a replication-deficient adeno-associated virus gene transfer vector expressing the human CLN2 cDNA to the brain of children with late infantile neuronal ceroid lipofuscinosis - Crystal, Ronald G; Sondhi, Dolan; Hackett, Neil R; Kaminsky, Stephen M; Worgall, Stefan; Stieg, Philip; Souweidane, Mark; Hosain, Syed; Heier, Linda; Ballon, Douglas; Dinner, Miles; Wisniewski, Krystyna; et al. (Human gene therapy, 2004)
Late infantile neuronal ceroid lipofuscinosis (LINCL) is a fatal childhood neurodegenerative lysosomal storage disease with no known therapy. There are estimated to be 200 to 300 children in the United States at any one time with the disease. LINCL is a genetic disease resulting from a deficiency of tripeptidyl peptidase I (TPP-I), a proteolytic enzyme encoded by CLN2, the gene that is mutated in individuals with LINCL. The subjects are chronically ill, with a progressive CNS disorder that invariably results in death, typically by age 8 to 12 years. The strategy of this clinical study is based on the concept that persistent expression in the CNS of the normal CLN2 cDNA with production of sufficient amounts of TPP-I should prevent further loss of neurons, and hence limit disease progression. To assess this concept, an adeno-associated virus vector (AAV2CUh-CLN2) will be used to transfer to and express the human CLN2 cDNA in the brain of children with LINCL. The vector consists of the AAV2 capsid enclosing the 4278-base single-stranded genome consisting of the two inverted terminal repeats of AAV serotype 2 and an expression cassette composed of the human cytomegalovirus (CMV) enhancer, the chicken beta-actin promoter/splice donor and 5' end of the intron, the 3' end of the rabbit P-globin intron and splice acceptor, the human CLN2 cDNA with an optimized Kozak translation initiation signal, and the polyadenylation/transcription stop codon from rabbit 3-globin. The proposed study will include 10 individuals and will be divided into two parts. Group A, to be studied first, will include four individuals with the severe form of the disease. Group B of the trial will include six individuals with a moderate form of the disease. After direct intracranial administration of the vector, there will be neurological assessment based on the LINCL clinical rating scale and magnetic resonance imaging/magnetic resonance spectroscopy assessment of the brain in regions of vector administration. The data generated will help evaluate two hypotheses: (1) that it is safe to carry out direct intracranial administration of the AAV2cuhCLN2 vector to the CNS of individuals with LINCL, and (2) that administration of the AAV2cuhCLN2 vector will slow down or halt the progression of the disease in the central nervous system.